Career choices among medical students in Bangladesh - Ahmed, SM Moslehuddin (Dove Medical Press, 2011)
INTRODUCTION: Information regarding career choices of medical students is important to plan human resources for health, design need-based educational programs, and ensure equitable and quality health care services in a country. AIM: The aim of the study is to identify career choices, nature of career, intended practice locations, and reasons for career choices of Bangladesh medical students. METHOD: First-, third-, and fifth-year students of Bangladesh Medical College and Uttara Adhunik Medical College completed a self-report questionnaire on career choices, nature of career, intended practice locations, and reasons for career choices. The students were requested to choose three long-term choices from the given specialties. RESULTS: A total of 132 students responded (46 males and 86 females) and response rate was 75%. The popular choices (first choice) among males and females were medical specialty, surgical specialty, obstetrics and gynecology, and general practice. For first, second, and third choices altogether, male students chose surgical specialties and female students preferred medical specialties. The leading reasons for selecting a specialty were personal interest and wide job opportunity. More than 67% of respondents wanted to join private services and about 90% chose major cities as practice locations. About 43% of respondents expressed willingness to practice medicine in Bangladesh, whereas 51% of total respondents wanted to practice abroad. DISCUSSION: Majority of students intended to specialize in established clinical specialties and subsequently practice in major cities, and more than half wanted to immigrate to other countries. Basic medical subjects and service-oriented (lifestyle-related) and preventive/social medical specialties were found to be less attractive. If this pattern continues, Bangladesh will suffer a chronic shortage of health personnel in certain specialties and in rural areas. CONCLUSIONS: Reorientation of health care and medical education is needed along with policy settings to attract doctors to the scarcity and high-priority disciplines so that imbalances encountered would be minimal in future.